Experiments and simulations on a thermosyphon solar collector with integrated storage. (October 2015) - Toninelli, P; Mariani, A; Del Col, D
Abstract: This paper deals with the thermal behaviour of a new type of flat solar collector that integrates the fluid storage tank. Often the main limitation of the solar thermosyphon installations is the prohibition to adopt external storage tanks due to their impact, especially for historical centres of particular architectural significance. To avoid this issue, a new system, that includes the collector and the storage, has been developed. This new apparatus works as a thermosyphon: it is possible to take advantage of the natural convection to avoid using a pump. Experimental tests have been conducted in such a collector with and without the absorbing plate. Furthermore, CFD simulations are reported to analyze in detail the dynamic thermal performance of the innovative solar collector and a good-agreement with the experimental tests has been found. Finally, both in numerical simulations and in experimental data the thermosyphon effect has been verified, obtaining the desired water temperature for domestic applications.